Development of a Pico-Hydro Trainer for Renewable Energy Practicum in Universities - Arwadi Sinuraya; Denny Haryanto Sinaga; Lastama Sinaga; Reza Arbi Azizi Lubis; Dito Yudhistira Nugroho; Ricky Nelson Tampubolon (Postgraduate, University of Mataram, 2026)
This study aimed to develop a Pico Hydro trainer as a practical learning tool to support renewable energy education in higher education. The development followed the ADDIE model, consisting of analysis, design, development, implementation, and evaluation phases. The trainer was constructed using essential components, including a turbine, AC generator, high-pressure pump, digital monitoring instruments, and safety features. Expert validation results indicated a feasibility score of 3.60 from the material expert, 3.50 from the media expert, and 3.56 from user responses, with an average rating of 3.55 that was categorized as “very feasible.” Performance testing demonstrated the trainer's ability to generate up to 22V at 576 RPM under no-load conditions. Additionally, student learning outcomes improved significantly, as shown by a normalized gain score of 0.714. These findings suggest that the Pico Hydro trainer is effective in integrating theoretical knowledge with hands-on experience, and it offers a safe, portable, and efficient solution for laboratory-based instruction in renewable energy systems.